Clinical-epidemiological study of caseous lymphadenitis in goats in the state of Pernambuco (Revista de Ciências Agroveterinárias, 2020)
Caseous lymphadenitis (CL), a contagious infectious disease caused by Corynebacterium pseudotuberculosis, stands out with great economic relevance for goat breeding in the country because it is one of the main causes of carcass condemnation and intense depreciation of the leather of small ruminants. The objective was to carry out a descriptive study of the clinical and epidemiological aspects of CL in goats in the state of Pernambuco and also to evaluate the detection of C. pseudotuberculosis in milk, blood, and stool samples by real-time PCR. Six hundred and forty-three goats were evaluated, of which 76 (11.8%) presented clinical signs suggestive of CL. And 88.9% (24/27) of the breeding was considered focus. Among symptomatic animals, 25 were selected and submitted to the collection of abscess content for bacteriological isolation. Milk, blood, and stool samples were analyzed for PLD gene detection by real-time polymerase chain reaction (PCR). Out of the 25 samples of abscess content, 72% (18/25) were positive. The PLD gene was detected in the frequencies of 8% (2/25) and 4% (1/25) in milk and blood samples, respectively. Caseous lymphadenitis is possibly widespread in the dairy herds of goats in the state of Pernambuco, especially in adult animals, with a higher occurrence of submandibular lymph node abscesses. The preliminary detection of C. pseudotuberculosis by mammary and hematogenous pathways may contribute to future approaches on the mechanisms of organic dissemination performed by the pathogen. However, it has little relevance to diagnosing the disease.
Keywords: Goats; Corynebacterium pseudotuberculosis; polymerase chain reaction